Appreciative of the Biomimicry Design Process for Revolutionary Furniture Development - Wan Noor Faaizah, Wan Omar; Khairul Aidil Azlin, Abd Rahman; Shafilla, Subri; Faryna, Mohd Khalis; Adibah, Yusuf; Hema Zulaika, Hashim; Nur Fadilah, Mohd Omar (2021)
The significance of biomimicry as a design methodology is discussed in this paper within the context of industrial design planning and design. For this research, the researcher has taken measures to validate the ontology of designers towards the “Biomimicry Design Process” (BDP) in order to discuss imitating nature to design sense. In the context of this study, biomimicry is the primary approach in assessing the designer's understanding of the design process from conceptual idea to visualised product. The strategies of (BDP) activities were applied to furniture design in order to bring a “Concept To Reality” (CTR). The various interpretations of transformation of idea development in (BDP) in furniture design have been discussed in both qualitative and quantitative research. Data has been gathered and analysed implicitly and explicitly from a designer's thought process to represent the main empirical data of previous studies. In this study, a stage of (BDP) was used: (1) Appreciation, (2) Emotion, (3) Transformation, and (4) Maximisation of Ideas.